Group WiM: A Group Navigation Technique for Collaborative Virtual Reality Environments - Chheang, Vuthea; Heinrich, Florian; Joeres, Fabian; Saalfeld, Patrick; Preim, Bernhard; Hansen, Christian (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
In this work, we present a group World-in-Miniature (WiM) navigation technique that allows a guide to navigate a team in collaborative virtual reality (VR) environments. We evaluated the usability, discomfort, and user performance of the proposed technique compared to state-of-the-art group teleportation in a user study {\left(n\,=\,21\right)} . The results show that the proposed technique induces less discomfort for the guide and has slight usability advantages. Additionally, the group WiM technique seems superior in regards to task completion time for obstructed target destination. However, it performs similarly to the group teleportation technique in direct line of sight cases. The group WiM technique provides potential benefits for effective group navigation in complex virtual environments and harder-to-reach target locations.